An experimental investigation of the effects of disclosure of compliance with IT security and control frameworks on individual investors' judgments. - Ong, Siyang. (2008)
This project provides empirical evidence on the effects of disclosure of compliance with established IT Security and Control Frameworks on individual investors’ perceptions and judgments on certain aspects of an organization.